Pengaruh Kerja Tim dan Motivasi terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening : (Studi Kasus PT. Venezia Footwear) - Rista Dwi Yana; Imam Baidlowi; Kasnowo Kasnowo (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of compensation, motivation, and work environment on employee performance with job satisfaction as an intervening variable at PT Venezia Footwear Jombang. The research approach used was explanatory quantitative, with the population covering all project employees. The sampling technique was carried out by purposive sampling, and data was collected through a questionnaire using the Likert scale. Data analysis was carried out using the Structural Equation Modeling (SEM) method to test the relationship between variables. The results of the study show that compensation, motivation, and work environment have a positive and significant influence on job satisfaction. In addition, compensation and motivation also have a positive and significant effect on employee performance, while the work environment does not show a significant influence on performance. Job satisfaction has been shown to mediate the influence of compensation and motivation on employee performance, but it does not mediate the influence of the work environment. These findings confirm that increased compensation and motivation are key factors in driving job satisfaction and employee performance. Although the work environment has no direct effect on performance, it still plays an important role in creating a supportive work environment. The practical implications of this study are the need for a managerial strategy that focuses on strengthening the compensation system and developing work motivation to increase productivity and employee satisfaction in a sustainable manner.